Effectiveness of Corticosteroid Injections in Reducing the Intensity of Pain in Patients with Plantar Fasciitis - Feroz Shah, Liaqat Khan, Adil Saidullah, Sayed Sohail Akhtar, Arshan Munir, Harris Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the effectiveness of corticosteroid injections in reducing the intensity of pain in patients with plantar fasciitis and assess its long-term outcomes. Methods: A prospective study was conducted on 72 patients diagnosed with plantar fasciitis, treated with corticosteroid injections. Pain intensity was assessed using the Visual Analog Scale (VAS) before treatment, at 1 week, 1 month, and 3 months post-injection. Statistical analyses included paired t-tests for pain reduction comparisons and logistic regression to analyze predictive factors for pain relief. Results: Pain intensity significantly reduced post-injection, with a mean VAS score decrease from 8.2 ± 1.0 pre-treatment to 4.5 ± 1.3 at 1 month (p < 0.001). However, the effect diminished after 3 months (VAS = 6.3 ± 1.2, p < 0.01). Logistic regression showed that the pre-treatment VAS score and age were significant predictors of pain reduction (p < 0.05). Conclusion: Corticosteroid injections provide significant short-term pain relief in patients with plantar fasciitis, but long-term efficacy remains uncertain. Factors such as age and baseline pain intensity may influence outcomes. Keywords: Plantar fasciitis, corticosteroid injection, pain reduction, Visual Analog Scale, long-term outcomes